Pura Eka Kahyangan Arena Kontestasi Identitas: Konflik Dan Rekonsiliasi Emik Umat Hindu Di Waode Angkalo, Sulawesi Tenggara - Putu Yoga Margaretsa; Ida Bagus Wika Krishna; Ni Luh Gede Hadriani (Jayapangus Press, 2025)
This study examines the internal conflict among Hindu transmigrants in Waode Angkalo Village, North Buton, regarding the interpretation of Pura Eka Kahyangan as a communal worship center. While some groups support the single-temple concept in line with PHDI policy, others advocate for the Tri Kahyangan system as an authentic representation of Balinese Hindu tradition. The research aims to analyze the dynamics of temple interpretation conflicts and explore emic-based resolutions emerging from community practices. A qualitative case study was employed, involving in-depth interviews, participant observation, and document analysis, with interactive data analysis through reduction, display, and conclusion drawing. Findings reveal that since 2007 the Hindu community has split into two factions supporters of Eka Kahyangan and Tri Kahyangan which by 2025 have grown to 32 and 97 households respectively. The conflict is driven by the persistence of Balinese traditions (sima), limited contextual understanding, functional dissatisfaction with the single temple, and political interests of local elites. Initially latent, the conflict evolved into a manifest struggle, turning the temple into a contested arena of identity, authority, and cultural legitimacy. Nevertheless, through the internalization of emic values such as ngayah, mutual cooperation, and deliberation, the temple continues to function as a multivocal symbol mediating tensions, sustaining social cohesion, and strengthening community resilience. This study highlights the significance of an emic approach in understanding intra-religious conflicts within transmigrant Hindu communities.